VULNERABILITY AND DISCRIMINATION UNDER BULGARIAN CONDITIONS: SOCIAL AND PSYCHOLOGICAL DIMENSIONS - Manov, Boris; Milenkova , Valentina (Revista Inclusiones, 2020)
The article considers vulnerability and discrimination, its state and factors for itsexistence throughidentifying and profiling the groups affected in the areas of healthcare, workplace, working conditions, social inclusion, equal opportunitie; and outlining the conditions that create different forms of discrimination. In the paper is presented the thesis that vulnerability is a prerequisite for discrimination because people at risk are in the situation of unequal treatment in society. The main features of social vulnerability and discrimination are related to the deficits in training andwork patterns; in the modification of employment contracts and forms of recruitment, as well as in the social inclusion.The article is based on the carried out In 2017 a national representative survey “Identifying and making profiles of groups and communities most affected by the risk of discrimination" in the implementation of Action 1 of the project "Prevention of discrimination and creating equal opportunities "BG05M9OP0013.003-0001-C001"“ with team leader prof.Valentina Milenkova.The sample included3600 individuals in the 18+ age group, and by collecting and analyzing representative national and regional (NUTS 2) empirical data.The main results show that the following groups are vulnerable and at risk of discrimination: unemployedpeople; individuals with low incomes andlow level of education; people over 55 years of age; individuals without national health insurance; ethnic minorities.